Metal-free carbon-based quantum material with strong room-temperature ferromagnetism and preparation method thereof

By thermal annealing and fluorinating the high-purity g-C3N4, the structural units of the carbon-nitrogen skeleton are broken and unmatched spins are formed, which solves the problems of low magnetic properties and poor stability of existing carbon-based ferromagnetic materials, and the preparation of metal-free carbon-based quantum materials with high Curie temperature and strong room temperature ferromagnetics is realized, which is suitable for many high-tech fields.

CN119873765AActive Publication Date: 2025-04-25XIDIAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510374219.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

The existing carbon-based ferromagnetic materials have problems of low magnetic properties and poor stability, which are difficult to produce on a large scale in the industry. The preparation process consumes high energy, high raw material costs, and serious environmental pollution.

Method used

High-purity g-C3N4 is used as raw material, and the adsorbed oxygen and structural oxygen are removed through two-step thermal annealing treatment. Then fluorinated with xenon difluoride, and thermal defluorination is carried out in argon, breaking the heptaazine structural unit, forming a cyano group and N-C=N bond, and introducing unpaired spins to enhance ferromagnetic coupling.

Benefits of technology

The metal-free carbon-based quantum materials prepared have high Curie temperature, strong room temperature ferromagnetic and high purity, and can be used in aerospace, biomedicine and other fields, with simple process and low energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873765A_ABST
    Figure CN119873765A_ABST
Patent Text Reader

Abstract

The invention discloses a metal-free carbon-based quantum material with strong room-temperature ferromagnetism and a preparation method thereof, and belongs to the technical field of quantum information materials, the material has a CN chain skeleton, a C = N bond and a cyano functional group, and the element ratio of C to N is (2.3-2.8): 1; the method comprises the steps that high-purity g-C3N4 powder serves as a raw material, oxygen-free g-C3N4 is obtained through deoxidizing annealing and vacuum annealing, then the oxygen-free g-C3N4 and xenon difluoride are subjected to calcination fluorination and standing, then thermal defluorination is conducted, and all the operations are conducted in an argon environment; in the thermal defluorination process, structural reconstruction occurs at the edge and the basal plane of a carbon-nitrogen skeleton, and high-density local spinning is introduced, so that ferromagnetic coupling between the spinning is excited, meanwhile, a graphite-like phase structure is destroyed, a molecular chain is formed, and the metal-free carbon-based quantum material with high Curie temperature and strong room-temperature ferromagnetism is obtained. The permanent magnet is a room-temperature non-metal spontaneous polarization permanent magnet and can be applied to the fields of spinning electronic devices, bioelectronic devices, medical detection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quantum information materials, and in particular relates to a metal-free carbon-based quantum material with strong room-temperature ferromagnetism and a preparation method thereof. Background Art

[0002] Traditional metal ferromagnetic materials, such as iron (Fe), cobalt (Co), nickel (Ni), etc., form the basis of modern industry, electronics and energy. Their magnetism comes from the interaction between the spin and exchange of 3d electrons, and the arrangement of magnetic domains can be finely regulated by an external magnetic field. However, traditional ferromagnetic metal materials face a series of defects that are difficult to ignore in actual production and application. For example, the high energy consumption and serious carbon emissions in the preparation process do not conform to the current industrial trend of green and low-carbon development; at the same time, they are highly dependent on rare metals, with high raw material costs and unstable supply; in addition, high-temperature smelting and complex heat treatment processes not only increase production costs, but also cause a lot of environmental pollution. In this context, carbon-based ferromagnetic materials have become an important development direction for solving the above problems due to their unique structure and properties. Carbon materials such as graphene, carbon nanotubes, diamond-like carbon films (DLC), etc. have low density, high specific strength, excellent chemical stability and biocompatibility, and are rich in resources and environmentally friendly. They have important research and application value in the new generation of electronic and sensor technologies. However, existing carbon-based ferromagnetic materials have the disadvantages of low magnetic properties and poor stability, making them difficult to produce on a large scale in industry.

[0003] Yong Wang et al. (Yong Wang, Yilv Guo, Zhaokun Wang, Lin Fu, Yu Zhang, Yongjie Xu, Shijun Yuan, Hongzhe Pan, Youwei Du, Jinlan Wang, and Nujiang Tang. Realization of Strong Room-Temperature Ferromagnetism in Atomically Thin 2D Carbon Nitride Sheets by Thermal Annealing. ACS Nano 2021, 15, 12069-12076) annealed carbon nitride to produce nitrogen vacancies and achieved room-temperature ferromagnetism with a high Curie temperature in carbon nitride. However, its saturation magnetization at room temperature was only 0.71emu / g. This technology is simple and easy to mass produce, but its product performance is poor, which limits its application in various fields.

[0004] Pin Lyu et al. (Pin Lyu, Ziying Wang, Na Guo, Jie Su, Jing Li, DongchenQi, Shibo Xi, Huihui Lin, Qihan Zhang, Stephen J. Pennycook, Jingsheng Chen, Xiaoxu Zhao, Chun Zhang, Kian Ping Loh, and Jiong Lu. Air-Stable Wafer-Scale Ferromagnetic Metallo-Carbon Nitride Monolayer. J. Am. Chem. Soc. 2024, 146, 20604-20614) synthesized an air-stable metal-carbon nitride monolayer by low-pressure chemical vapor deposition, which has ultra-dense single magnetic atoms and exhibits room-temperature ferromagnetism. However, this method has a complex preparation process, high production cost, and requires the introduction of metal elements, making its magnetism susceptible to environmental influences, and essentially cannot solve the problems of ferromagnetic energy consumption, resources and pollution. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a metal-free carbon-based quantum material with strong room temperature ferromagnetism and a preparation method thereof, using high-purity g-C3N4 as a raw material, removing adsorbed oxygen and structural oxygen through a two-step thermal annealing treatment, and then using xenon difluoride to fluorinate in a sealed reactor, and then thermally defluorinate in argon. During the thermal defluorination process, the heptazine structural unit at the edge of the fluorinated carbon nitride is broken to form a cyano group, while an NC=N bond is introduced to generate a dangling bond; the N atom is lost on the basal plane to form a CC chemical bond, and both structural reconstructions cause the carbon atoms to produce unpaired spins, thereby introducing a local magnetic moment and enhancing ferromagnetic coupling, thereby obtaining a metal-free carbon-based quantum material. The material has the characteristics of high purity, high Curie temperature and strong room-temperature ferromagnetism, and is a room-temperature non-metallic spontaneously polarized permanent magnet. Its performance can enable the metal-free carbon-based material to be practically applied in aerospace, biomedicine, spin electronics and other magnetic fields. It is a key material for the research and development of carbon-based room-temperature ferromagnetism in sp electron systems, and is conducive to the manufacture of lightweight magnetic equipment and the application and development of spin electronics devices and bioelectronic devices. The preparation method of the present invention has the characteristics of simple process and easy repeatability.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism comprises the following steps: Step 1: calcining and fluorinating oxygen-free g-C3N4 powder and xenon difluoride sealed in a reaction kettle in an argon environment, opening the reaction kettle in an argon environment after natural cooling to room temperature, and standing for 1-3 hours to obtain fluorinated carbon nitride; the mass ratio of the oxygen-free g-C3N4 powder to xenon difluoride is 1: (4-5); Step 2: thermally defluorinating the fluorinated carbon nitride in an argon environment, and naturally cooling to room temperature to obtain defluorinated carbon nitride; Step 3: Magnetize the defluorinated carbon nitride to obtain a black powder adsorbed on the surface of the magnet, which is a metal-free carbon-based quantum material with strong room temperature ferromagnetism.

[0007] The preparation method of the oxygen-free g-C3N4 powder is: The high-purity g-C3N4 powder was deoxidized and annealed in an argon environment, and then cooled to room temperature under a pressure of less than 5×10 -4 Pa in a negative pressure environment, and then naturally cool to room temperature to obtain oxygen-free g-C3N4 powder; wherein, the deoxygenation annealing conditions are: heating to 550-650°C at 2.5-5°C / min and then keeping warm for 2-4h; the vacuum annealing conditions are: heating to 600-650°C at 2.5-5°C / min and then keeping warm for 2-4h; the content of metal elements in the high-purity g-C3N4 powder is less than 0.001%.

[0008] The calcination and fluorination conditions in step 1 are: heating to 180-200° C. at a rate of ≥1° C. / min and then calcining and fluorinating for 24-36 hours.

[0009] The thermal defluorination conditions in step 2 are: in 50-300cc / min argon, heating to 660-700°C at 20-30°C / min and then keeping the temperature for 5-15 minutes.

[0010] In the step 3, an electromagnet with a suction density of more than 100 kPa is used to perform magnetic field screening on the defluorinated carbon nitride after magnetization treatment, so as to screen out the black powder adsorbed on the surface of the magnet.

[0011] The present invention also provides a metal-free carbon-based quantum material with strong room temperature ferromagnetism prepared by the above preparation method.

[0012] The structural formula of the metal-free carbon-based quantum material is: The structure has a CN chain skeleton, a C=N bond and a cyano functional group; the metal-free carbon-based quantum material is a black powder at the macroscopic level and a long strip crystal morphology or a quadrilateral block crystal morphology at the microscopic level.

[0013] The C:N element ratio of the metal-free carbon-based quantum material is (2.3-2.8):1.

[0014] The metal-free carbon-based quantum material has room temperature ferromagnetism; the saturation magnetization at room temperature is 10.9-18.7emu / g, and the residual magnetization is 1.7-2.6emu / g; the saturation magnetization at 2K is 15.4-25.2emu / g, and the residual magnetization is 2.8-4.8emu / g.

[0015] The present invention also provides the application of the metal-free carbon-based quantum material with strong room temperature ferromagnetism in spin electronic devices, bioelectronic devices and medical detection.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention obtains a metal-free carbon-based quantum material with strong room temperature ferromagnetism by reacting oxygen-free g-C3N4 with xenon difluoride at high temperature and then performing a thermal defluorination treatment in an argon environment. The heptazine structural unit at the edge of the fluorinated carbon nitride is broken to form a cyano group and a NC=N bond, generating a dangling bond; and the N atom is lost on the basal plane to form a CC chemical bond, and the p of the carbon atom is z The orbitals are in an unsaturated state, and both provide unpaired spins; the high density of localized spins excites ferromagnetic coupling between spins, resulting in strong ferromagnetism at room temperature.

[0017] 2. The metal-free carbon-based quantum material prepared by the present invention has strong room-temperature ferromagnetism, and its Curie temperature is as high as 879.5K. When the temperature is 2K, the saturation magnetization is not less than 15.4emu / g, and can reach up to 25.2emu / g. The residual magnetization is not less than 2.8emu / g, and can reach up to 4.8emu / g; when the temperature is 300K, the saturation magnetization is not less than 10.9emu / g, and can reach up to 18.7emu / g, and the residual magnetization is not less than 1.7emu / g, and can reach up to 2.6emu / g; the metal-free carbon-based quantum material prepared by the preparation method of the present invention has an applicable high Curie temperature and strong room-temperature ferromagnetism, and is a room-temperature non-metallic spontaneously polarized permanent magnet, which can replace traditional metal alloys or oxide ferromagnetic materials, and is used in a wide range of magnetic demand scenarios, especially in aerospace, biomedicine, environmental protection and other fields that require lightweight, metal-free, biocompatible, green and degradable, and can also be used in spin electronic devices, topological quantum devices and magnetic storage.

[0018] 3. The preparation method of the present invention can prepare intrinsic carbon-based ferromagnetic materials with high Curie temperature and high magnetization intensity that can be used in practice. Compared with the preparation of traditional ferromagnetic materials, the method requires a wide range of raw materials, among which g-C3N4 can be prepared by common chemical raw materials such as urea, melamine, and dicyandiamide; the method requires extremely low energy consumption, the maximum thermal annealing temperature is only 700°C, and the duration is short; the ferromagnetic material prepared by this method has the characteristics of low density, strong chemical stability and good biocompatibility of carbon-based materials, which are not available or difficult to achieve in traditional metal ferromagnetic materials.

[0019] 4. The present invention obtains oxygen-free g-C3N4 by subjecting high-purity g-C3N4 powder to a two-step thermal annealing treatment, thereby avoiding the non-ferromagnetic impurity phase induced by the oxygen element during the synthesis process and promoting the formation of a long-range magnetic ordered structure in the metal-free carbon-based quantum material; the preparation method of the present invention is carried out in an argon environment, avoiding the influence of nitrogen, oxygen, and water, so that the element ratio in the final product is controllable.

[0020] In summary, the present invention uses high-purity g-C3N4 as a raw material, removes adsorbed oxygen and structural oxygen by heat treatment, fluorinates with xenon difluoride and then performs thermal defluorination to obtain a metal-free carbon-based quantum material. The material has an applicable high Curie temperature and strong room-temperature ferromagnetism, is a room-temperature non-metallic spontaneously polarized permanent magnet, and has the characteristics of light weight, chemical stability, and biocompatibility. The raw materials required for the method of the present invention are widely available and have extremely low energy consumption. The metal-free carbon-based material obtained by the method can be widely used in the field of magnetic applications and quantum information, is a key material for the research and development of carbon-based room-temperature ferromagnetism in sp electron systems, and is conducive to the application and development of aerospace, biomedicine, and spin electronics. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1a This is a real optical photograph of the metal-free carbon-based quantum material prepared in Example 1.

[0022] Figure 1b This is a real optical photograph of the metal-free carbon-based quantum material prepared in Example 1 when not affected by a magnetic field.

[0023] Figure 1c This is a real optical photograph of the metal-free carbon-based quantum material prepared in Example 1 being attracted by a NdFeB magnet at a close distance.

[0024] Figure 1d This is a real optical photograph of the metal-free carbon-based quantum material prepared in Example 1 being attracted by a NdFeB magnet at a long distance.

[0025] Figure 2a This is a SEM image of the metal-free carbon-based quantum material prepared in Example 1 with a long crystal morphology.

[0026] Figure 2b This is a SEM image of the metal-free carbon-based quantum material prepared in Example 1 with a quadrilateral block-shaped crystal morphology.

[0027] Figure 3a This is the XPS spectrum of the nitrogen element in the metal-free carbon-based quantum material prepared in Example 1.

[0028] Figure 3b This is the XPS spectrum of the carbon element in the metal-free carbon-based quantum material prepared in Example 1.

[0029] Figure 4a This is the full XPS spectrum of the metal-free carbon-based quantum material prepared in Example 1.

[0030] Figure 4b This is the full XPS spectrum of the metal-free carbon-based quantum material prepared in Example 2.

[0031] Figure 5 This is the MT curve of the metal-free carbon-based quantum material prepared in Example 1.

[0032] Figure 6a This is the MH curve of the metal-free carbon-based quantum material prepared in Example 1 at 2K.

[0033] Figure 6b This is the MH curve of the metal-free carbon-based quantum material prepared in Example 1 at 300K.

[0034] Figure 7a This is the MH curve of the metal-free carbon-based quantum material prepared in Example 2 at 2K.

[0035] Figure 7b This is the MH curve of the metal-free carbon-based quantum material prepared in Example 2 at 300K.

[0036] Figure 8 This is a magnetic field distribution diagram of the metal-free carbon-based quantum material powder particles prepared in Example 1 at room temperature in the atmosphere. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and embodiments.

[0038] The structural formula of the metal-free carbon-based quantum material with strong room temperature ferromagnetism provided by the present invention is: The structure has a CN chain skeleton, a C=N bond and a cyano functional group; the carbon-based material is a molecular chain with a two-dimensional structure; it appears as a black powder at a macroscopic level and can be attracted by an external magnetic field; at a microscopic level, it has a long strip-shaped crystal morphology or a quadrilateral block-shaped crystal morphology, and is a room temperature non-metallic spontaneously polarized permanent magnet.

[0039] The invention discloses a method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism. The method uses high-purity g-C3N4 as a raw material, and sequentially performs deoxidation, fluorination, thermal defluorination and magnetization treatment, and all operations are performed in an argon environment. During the thermal defluorination process, structural reconstruction occurs at the edge and basal plane of the carbon-nitrogen skeleton, high-density localized spins are introduced, and a large number of unpaired spins are generated, thereby stimulating ferromagnetic coupling between spins. At the same time, the graphite-like phase structure is destroyed to form a molecular chain. After screening, a metal-free carbon-based quantum material with strong room temperature ferromagnetism is obtained. The method specifically comprises the following steps: Step 1: In an argon-filled glove box, weigh an appropriate amount of high-purity g-C3N4 powder and put it into a crucible, then transfer it to a muffle furnace in an argon atmosphere for deoxidation annealing, heat it to 550-650℃ at 2.5-5℃ / min, keep it warm for 2-4h, cool it naturally to room temperature, and then transfer it to an argon-filled tube furnace for vacuum annealing. Use a vacuum pump to evacuate the pressure in the tube furnace to less than 5×10 -4 Pa, then heated to 600-650°C at 2.5-5°C / min, and then kept warm for 2-4h, and naturally cooled to room temperature to obtain oxygen-free g-C3N4 powder, which was stored in an argon-filled glove box; the content of metal elements in the high-purity g-C3N4 powder used should not be higher than 0.001%; ​​the present invention performs deoxygenation annealing on the high-purity g-C3N4, which can remove adsorbed oxygen and structural oxygen in the raw material, and avoid oxygen elements inducing additional non-ferromagnetic impurity phases during the synthesis process; Step 2: In an argon-filled glove box, first place 200 mg of oxygen-free g-C3N4 powder in a polytetrafluoroethylene reactor liner, then place 800-1000 mg of xenon difluoride, then immediately seal the reactor, transfer the reactor to a muffle furnace, heat to 180-200°C at a rate of ≥1°C / min, and then calcine and fluorinate for 24-36 hours. After naturally cooling to room temperature, open the reactor in an argon-filled glove box and let it stand for 1-3 hours to eliminate side reactions and release residual fluoride on the surface to obtain fluorinated carbon nitride; Step 3: In an argon-filled glove box, the fluorinated carbon nitride is placed in a crucible, and then transferred to an argon-filled tube furnace for thermal defluorination. The tube furnace is kept at 50-300cc / min of argon gas, and the temperature is increased to 660-700°C at 20-30°C / min, and then kept at this temperature for 5-15min. After naturally cooling to room temperature, defluorinated carbon nitride is obtained; Step 4: Use a DC magnetization device to magnetize the defluorinated carbon nitride, and then use an electromagnet with a suction density ≥ 100 kPa to attract the magnetized defluorinated carbon nitride, sieve out the unattracted powder, and obtain a metal-free carbon-based quantum material with strong room temperature ferromagnetism.

[0040] Example 1

[0041] A metal-free carbon-based quantum material with strong room-temperature ferromagnetism. The metal-free carbon-based quantum material is a molecular chain with a two-dimensional structure. It appears as a black powder at a macroscopic level and can be attracted by an external magnetic field. At a microscopic level, it appears as long strip crystals or quadrilateral block crystals. The saturation magnetization intensity at room temperature is 18.7emu / g, and the residual magnetization intensity is 2.6emu / g; at 2K, the saturation magnetization intensity is 25.2emu / g, and the residual magnetization intensity is 4.8emu / g.

[0042] The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism specifically comprises the following steps: Step 1: In an argon-filled glove box, weigh an appropriate amount of high-purity g-C3N4 powder and put it into a crucible, then transfer it to a muffle furnace in an argon atmosphere, heat it to 550°C at 2.5°C / min, keep it warm for 2h, cool it naturally to room temperature, and then transfer it to an argon-filled tube furnace. Use a vacuum pump to evacuate the pressure in the tube furnace to 2×10 -5 Pa, then heated to 600 °C at 2.5 °C / min and kept at this temperature for 2 h. After naturally cooling to room temperature, oxygen-free g-C3N4 powder was obtained and stored in an argon-filled glove box. Step 2: In an argon-filled glove box, first place 200 mg of oxygen-free g-C3N4 powder in a polytetrafluoroethylene reactor liner, then place 1000 mg of xenon difluoride, then immediately seal the reactor, transfer the reactor to a muffle furnace, heat it to 180°C at a heating rate of 5°C / min, and then calcine and fluorinate for 36 hours. After naturally cooling to room temperature, open the reactor in an argon-filled glove box and let it stand for 1 hour to obtain fluorinated carbon nitride; Step 3: In an argon-filled glove box, the fluorinated carbon nitride is transferred to a crucible, and then transferred to an argon-filled tube furnace. The tube furnace is kept at 50cc / min of argon gas, and the temperature is increased to 660°C at 20°C / min and then kept for 15 minutes. After naturally cooling to room temperature, the defluorinated carbon nitride is obtained and stored in an atmospheric environment; Step 4: Use a DC magnetization device to magnetize the defluorinated carbon nitride, and then use an electromagnet with a suction density of 100 kPa to attract the magnetized defluorinated carbon nitride, sieve out the unattracted powder, and obtain a metal-free carbon-based quantum material with strong room temperature ferromagnetism.

[0043] Example 2

[0044] A metal-free carbon-based quantum material with strong room-temperature ferromagnetism. The metal-free carbon-based quantum material is a molecular chain with a two-dimensional structure. It appears as a black powder at a macroscopic level and can be attracted by an external magnetic field. At a microscopic level, it appears as long strip crystals or quadrilateral block crystals. The saturation magnetization intensity at room temperature is 10.9emu / g, and the residual magnetization intensity is 1.7emu / g; the saturation magnetization intensity at 2K is 15.4emu / g, and the residual magnetization intensity is 2.8emu / g.

[0045] The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism specifically comprises the following steps: Step 1: In an argon-filled glove box, weigh an appropriate amount of high-purity g-C3N4 powder and put it into a crucible, then transfer it to a muffle furnace in an argon atmosphere, heat it to 650°C at 5°C / min, keep it warm for 4h, cool it naturally to room temperature, transfer it to an argon-filled tube furnace, and use a vacuum pump to evacuate the pressure in the tube furnace to 5×10 -5 Pa, then heated to 650 °C at 5 °C / min and kept at that temperature for 4 h. After naturally cooling to room temperature, oxygen-free g-C3N4 powder was obtained and stored in an argon-filled glove box. Step 2: In an argon-filled glove box, first place 200 mg of oxygen-free g-C3N4 powder in a polytetrafluoroethylene reactor liner, then place 800 mg of xenon difluoride, and then immediately seal the reactor, transfer the reactor to a muffle furnace, heat it to 200°C at a heating rate of 1°C / min, and then calcine and fluorinate for 24 hours. After naturally cooling to room temperature, open the reactor in an argon-filled glove box and let it stand for 3 hours to obtain fluorinated carbon nitride; Step 3: In an argon-filled glove box, the fluorinated carbon nitride is transferred to a crucible, and then transferred to an argon-filled tube furnace. The tube furnace is kept at 100cc / min of argon gas, and the temperature is increased to 700°C at 30°C / min and then kept at this temperature for 5 minutes. After naturally cooling to room temperature, the defluorinated carbon nitride is obtained and stored in an atmospheric environment; Step 4: Use a DC magnetization device to magnetize the defluorinated carbon nitride, and then use an electromagnet with a suction density of 200 kPa to attract the magnetized defluorinated carbon nitride, sieve out the unattracted powder, and obtain a metal-free carbon-based quantum material with strong room temperature ferromagnetism.

[0046] Example 3

[0047] A metal-free carbon-based quantum material with strong room-temperature ferromagnetism. The metal-free carbon-based quantum material is a molecular chain with a two-dimensional structure. It appears as a black powder at a macroscopic level and can be attracted by an external magnetic field. At a microscopic level, it appears as long strip crystals or quadrilateral block crystals. The saturation magnetization intensity at room temperature is 13.6emu / g, and the residual magnetization intensity is 1.9emu / g; at 2K, the saturation magnetization intensity is 17.1emu / g, and the residual magnetization intensity is 3.5emu / g.

[0048] The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism specifically comprises the following steps: Step 1: In an argon-filled glove box, weigh an appropriate amount of high-purity g-C3N4 powder and put it into a crucible, then transfer it to a muffle furnace in an argon atmosphere, heat it to 575°C at 3°C / min, keep it warm for 3h, cool it naturally to room temperature, and then transfer it to an argon-filled tube furnace. Use a vacuum pump to evacuate the pressure in the tube furnace to 1×10 -4Pa, then heated to 625 °C at 3 °C / min and kept at that temperature for 3 h, and naturally cooled to room temperature to obtain oxygen-free g-C3N4 powder, which was stored in an argon-filled glove box; Step 2: In an argon-filled glove box, first place 200 mg of oxygen-free g-C3N4 powder in a polytetrafluoroethylene reactor liner, then place 850 mg of xenon difluoride, and then immediately seal the reactor, transfer the reactor to a muffle furnace, heat it to 185°C at a heating rate of 10°C / min, and then calcine and fluorinate for 27 hours. After naturally cooling to room temperature, open the reactor in an argon-filled glove box and let it stand for 2 hours to obtain fluorinated carbon nitride; Step 3: In an argon-filled glove box, the fluorinated carbon nitride is transferred to a crucible, and then transferred to an argon-filled tube furnace. The tube furnace is kept at 150cc / min of argon gas, and the temperature is increased to 670°C at 23°C / min and then kept at this temperature for 8 minutes. After naturally cooling to room temperature, the defluorinated carbon nitride is obtained and stored in an atmospheric environment; Step 4: Use a DC magnetization device to magnetize the defluorinated carbon nitride, and then use an electromagnet with a suction density of 300 kPa to attract the magnetized defluorinated carbon nitride, sieve out the unattracted powder, and obtain a metal-free carbon-based quantum material with strong room temperature ferromagnetism.

[0049] Example 4

[0050] A metal-free carbon-based quantum material with strong room-temperature ferromagnetism. The metal-free carbon-based quantum material is a molecular chain with a two-dimensional structure. It appears as a black powder at a macroscopic level and can be attracted by an external magnetic field. At a microscopic level, it appears as long strip crystals or quadrilateral block crystals. The saturation magnetization intensity at room temperature is 15.4emu / g, and the residual magnetization intensity is 2.3emu / g; the saturation magnetization intensity at 2K is 19.3emu / g, and the residual magnetization intensity is 3.9emu / g.

[0051] The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism specifically comprises the following steps: Step 1: In an argon-filled glove box, weigh an appropriate amount of high-purity g-C3N4 powder and put it into a crucible, then transfer it to a muffle furnace in an argon atmosphere, heat it to 600°C at 4°C / min, keep it warm for 3.5h, cool it naturally to room temperature, and then transfer it to an argon-filled tube furnace. Use a vacuum pump to evacuate the pressure in the tube furnace to 3×10 -4 Pa, then heated to 610 °C at 4 °C / min and kept at this temperature for 3.5 h. After naturally cooling to room temperature, oxygen-free g-C3N4 powder was obtained and stored in an argon-filled glove box. Step 2: In an argon-filled glove box, first place 200 mg of oxygen-free g-C3N4 powder in a polytetrafluoroethylene reactor liner, then place 900 mg of xenon difluoride, and then immediately seal the reactor, transfer the reactor to a muffle furnace, heat it to 190°C at a heating rate of 8°C / min, and then calcine and fluorinate for 30 hours. After naturally cooling to room temperature, open the reactor in an argon-filled glove box and let it stand for 1.5 hours to obtain fluorinated carbon nitride; Step 3: In an argon-filled glove box, the fluorinated carbon nitride is transferred to a crucible, and then transferred to an argon-filled tube furnace. The tube furnace is kept at 200cc / min of argon gas, and the temperature is increased to 680°C at 25°C / min and then kept for 10 minutes. After naturally cooling to room temperature, the defluorinated carbon nitride is obtained and stored in an atmospheric environment; Step 4: Use a DC magnetization device to magnetize the defluorinated carbon nitride, and then use an electromagnet with a suction density of 400 kPa to attract the magnetized defluorinated carbon nitride, sieve out the unattracted powder, and obtain a metal-free carbon-based quantum material with strong room temperature ferromagnetism.

[0052] Example 5

[0053] A metal-free carbon-based quantum material with strong room-temperature ferromagnetism. The metal-free carbon-based quantum material is a molecular chain with a two-dimensional structure. It appears as a black powder at a macroscopic level and can be attracted by an external magnetic field. At a microscopic level, it appears as long strip crystals or quadrilateral block crystals. The saturation magnetization at room temperature is 16.6emu / g, and the residual magnetization is 2.1emu / g. At 2K, the saturation magnetization is 22.5emu / g, and the residual magnetization is 4.3emu / g.

[0054] The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism specifically comprises the following steps: Step 1: In an argon-filled glove box, weigh an appropriate amount of high-purity g-C3N4 powder and put it into a crucible, then transfer it to a muffle furnace in an argon atmosphere, heat it to 625°C at 3.5°C / min, keep it warm for 2.5h, cool it naturally to room temperature, and then transfer it to an argon-filled tube furnace. Use a vacuum pump to evacuate the pressure in the tube furnace to 5×10 -4 Pa, then heated to 640 °C at 3.5 °C / min and kept at this temperature for 2.5 h. After naturally cooling to room temperature, oxygen-free g-C3N4 powder was obtained and stored in an argon-filled glove box. Step 2: In an argon-filled glove box, first place 200 mg of oxygen-free g-C3N4 powder in a polytetrafluoroethylene reactor liner, then place 950 mg of xenon difluoride, and then immediately seal the reactor, transfer the reactor to a muffle furnace, heat it to 195°C at a heating rate of 3°C / min, and then calcine and fluorinate for 33 hours. After naturally cooling to room temperature, open the reactor in an argon-filled glove box and let it stand for 2.5 hours to obtain fluorinated carbon nitride; Step 3: In an argon-filled glove box, the fluorinated carbon nitride was transferred to a crucible, and then transferred to an argon-filled tube furnace. The tube furnace was kept at 300cc / min of argon gas, and the temperature was increased to 690°C at 28°C / min and then kept at that temperature for 13 minutes. After naturally cooling to room temperature, the defluorinated carbon nitride was obtained and stored in an atmospheric environment; Step 4: Use a DC magnetization device to magnetize the defluorinated carbon nitride, then use an electromagnet with a suction density of 500 kPa to attract the magnetized defluorinated carbon nitride, sieve out the unattracted powder, and obtain a metal-free carbon-based quantum material with strong room temperature ferromagnetism.

[0055] The metal-free carbon-based quantum materials with strong room-temperature ferromagnetism prepared in the above embodiments can be used in spin electronic devices, bioelectronic devices and medical detection.

[0056] like Figure 1a As shown, the metal-free carbon-based quantum material prepared in Example 1 is a black powder; Figure 1b The state of the metal-free carbon-based quantum material prepared in Example 1 when not affected by a magnetic field, Figure 1c It shows that the metal-free carbon-based quantum material prepared in Example 1 is attracted by the NdFeB magnet at a close distance. Figure 1d It shows that the metal-free carbon-based quantum material prepared in Example 1 is attracted by the NdFeB magnet at a long distance, which intuitively proves that the metal-free carbon-based quantum material prepared in Example 1 has strong room temperature ferromagnetism.

[0057] like Figure 2a and Figure 2b As shown, it can be seen from the SEM image that the metal-free carbon-based quantum material prepared in Example 1 is a long strip crystal or a quadrilateral block crystal, which is consistent with the crystal characteristics of the chain molecular structure.

[0058] like Figure 3a and Figure 3b As shown, the metal-free carbon-based quantum material prepared in Example 1 contains chemical bonds in different states, that is, NC3, CN=C, N=CN and a large number of CC bonds exist at the same time, revealing that the graphite-like phase structure is broken to form a chain structure.

[0059] like Figure 4a As shown, the ratio of C element to N element in the metal-free carbon-based quantum material prepared in Example 1 is 2.8:1; Figure 4b As shown, the ratio of C element to N element in the metal-free carbon-based quantum material prepared in Example 2 is 2.3:1, indicating that the metal-free carbon-based quantum material loses a large number of nitrogen atoms relative to g-C3N4.

[0060] As shown in Table 1, the metal-free carbon-based quantum material prepared in Example 1 does not contain any magnetic metal at a level of one part per million (accuracy of ICP-OES), which proves that the ferromagnetism of the metal-free carbon-based quantum material is an intrinsic property.

[0061] Table 1 ICP-OES results of metal-free carbon-based quantum materials prepared in Example 1 like Figure 5 As shown, the MT curve of the metal-free carbon-based quantum material prepared in Example 1 under an external magnetic field of 1000 Oe shows that the saturation magnetization intensity decreases rapidly at 879.5 K, indicating that the metal-free carbon-based quantum material has ferromagnetism and the Curie temperature is 879.5 K.

[0062] like Figure 6a As shown, the saturation magnetization intensity of the metal-free carbon-based quantum material prepared in Example 1 at 2K M S The residual magnetization is 25.16emu / g. M r 4.82emu / g, coercive field H C is 553Oe; Figure 6b As shown, the saturation magnetization at 300K M S The residual magnetization is 18.72emu / g. M r 2.59emu / g, coercive field H C It is 233Oe; compared with the existing two-dimensional carbon-based materials, the metal-free carbon-based quantum material prepared by the present invention has a high saturation magnetization intensity and has magnetic properties that can be used in practical applications at room temperature.

[0063] like Figure 7a As shown, the saturation magnetization intensity of the metal-free carbon-based quantum material prepared in Example 2 at 2K M S The residual magnetization is 15.4emu / g. M r 2.79emu / g, coercive field H C is 562Oe; Figure 7b As shown, the saturation magnetization at 300K M S The residual magnetization is 10.9emu / g. M r 1.69emu / g, coercive field H CIt is 300Oe; compared with the existing two-dimensional carbon-based materials, it is shown that the metal-free carbon-based quantum material prepared by the present invention has a high saturation magnetization intensity and has magnetic properties that can be actually applied at room temperature.

[0064] like Figure 8 As shown, the 500 nm particle size agglomerated powder of the metal-free carbon-based quantum material prepared in Example 1 has obvious NS magnetic poles under room temperature and atmospheric environment, which proves that the metal-free carbon-based quantum material prepared in the present invention is a permanent magnet with spontaneous magnetization characteristics at room temperature.

Claims

1. A method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism, characterized in that: The following steps are involved: Step 1: calcining and fluorinating oxygen-free g-C3N4 powder and xenon difluoride sealed in a reaction kettle in an argon environment, opening the reaction kettle in an argon environment after natural cooling to room temperature, and standing for 1-3 hours to obtain fluorinated carbon nitride; the mass ratio of the oxygen-free g-C3N4 powder to xenon difluoride is 1: (4-5); Step 2: thermally defluorinating the fluorinated carbon nitride in an argon environment, and naturally cooling to room temperature to obtain defluorinated carbon nitride; Step 3: Magnetize the defluorinated carbon nitride to obtain a black powder adsorbed on the surface of the magnet, which is a metal-free carbon-based quantum material with strong room temperature ferromagnetism.

2. The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 1, characterized in that: The preparation method of the oxygen-free g-C3N4 powder is: The high-purity g-C3N4 powder was deoxidized and annealed in an argon environment, and then cooled to room temperature under a pressure of less than 5×10 -4 Pa in a negative pressure environment, and then naturally cool to room temperature to obtain oxygen-free g-C3N4 powder; wherein, the deoxygenation annealing conditions are: heating to 550-650°C at 2.5-5°C / min and then keeping warm for 2-4h; the vacuum annealing conditions are: heating to 600-650°C at 2.5-5°C / min and then keeping warm for 2-4h; the content of metal elements in the high-purity g-C3N4 powder is less than 0.001%.

3. The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 1, characterized in that: The calcination and fluorination conditions in step 1 are: heating to 180-200° C. at a rate of ≥1° C. / min and then calcining and fluorinating for 24-36 hours.

4. The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 1, characterized in that: The thermal defluorination conditions in step 2 are: in 50-300cc / min argon, heating to 660-700°C at 20-30°C / min and then keeping the temperature for 5-15 minutes.

5. The method for preparing a metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 1, characterized in that: In the step 3, an electromagnet with a suction density of at least 100 kPa is used to perform magnetic field screening on the defluorinated carbon nitride after magnetization treatment, so as to screen out the black powder adsorbed on the surface of the magnet.

6. A metal-free carbon-based quantum material with strong room temperature ferromagnetism obtained according to the preparation method according to any one of claims 1 to 5.

7. The metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 6, characterized in that: The structural formula of the metal-free carbon-based quantum material is: The structure has a CN chain skeleton, a C=N bond and a cyano functional group; the metal-free carbon-based quantum material is a black powder at the macroscopic level and a long strip crystal morphology or a quadrilateral block crystal morphology at the microscopic level.

8. The metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 6, characterized in that: The C:N element ratio of the metal-free carbon-based quantum material is (2.3-2.8):

1.

9. The metal-free carbon-based quantum material with strong room temperature ferromagnetism according to claim 6, characterized in that: The metal-free carbon-based quantum material has room temperature ferromagnetism; the saturation magnetization at room temperature is 10.9-18.7emu / g, and the residual magnetization is 1.7-2.6emu / g; the saturation magnetization at 2K is 15.4-25.2emu / g, and the residual magnetization is 2.8-4.8emu / g.

10. Application of the metal-free carbon-based quantum material with strong room temperature ferromagnetism as claimed in any one of claims 7 to 9 in spin electronic devices, bioelectronic devices and electromagnetic communications.

Citation Information

Patent Citations

  • Preparation method for ferromagnetic B-doped g-C3N4 two-dimensional ultrathin nanosheet

    CN106006583A

  • Carbon-based confinement interface supported palladium monatomic catalyst and preparation method thereof

    CN111659444A

  • Monatomic catalyst for catalytic reforming of tar and preparation parameter optimization method of monatomic catalyst

    CN114405532A

  • Method of preparing improved magnetic material

    GB985930A

  • Rotating machine with sintered magnet, and method of manufacturing sintered magnet

    JP2010034365A